Britain's economic blockade of Germany, 1914-1919 - Osborne, Eric W. (London ; New York : Frank Cass, 2004)
Great Britain's economic blockade of Germany in World War I was one of the key elements to the victory of the Entente. Though Britain had been the leading exponent of blockades for two centuries, the World War I blockade was not effective at the outbreak of hostilities. Pre-war changes had led to the Admiralty supplanting the Royal Navy's leadership role in favour of direction from the civilian branch of government on the basis of international law. The struggle between the primacy of international law and military expediency lasted for nearly two years, as the British tried to reconcile the.
Book Cover; Title; Contents; Series Editor's Preface; Acknowledgments; Introduction; Foreign Policy, Naval Commitments, and the Changes to Blockade, 1756 1904; The Culmination of Faith in International Law: The Second Hague Conference and the Declaration of London, 1905 11; Blockade Preparations in the Final Years of Peace, 1911 14; Britain at War: The First Steps for Blockade in 1914; The Year of Frustration, Stalemate, and Doubt, 1915; The Blockade Strengthens, 1916; The Critical Year, 1917; The Last Year of War, and the Final Legacy of the Blockade in the Peace, 1918 July 1919.
Includes bibliographical references (pages 195-208) and index.
Print version record.
eBooks on EBSCOhost
Keywords: World War, 1914-1918 -- Blockades -- Germany; World War, 1914-1918 -- Naval operations, British; Great Britain -- Foreign economic relations -- Germany -- History -- 20th century; Germany -- Foreign economic relations -- Great Britain -- History -- 20th century; Guerre mondiale, 1914-1918 -- Blocus -- Allemagne; HISTORY -- Military -- World War I; Blockade; International economic relations; Germany; Great Britain; Första världskriget 1914-1918.; Blockad -- historia; 1900-1999; Electronic books; History